The quality management of Chinese real estate landscape project / Gu Hongming - Gu, Hongming (2022)
With globalization and urbanization, people's demand for the urban environment and living environment is more diversified. The requirements for the quality of landscape design are becoming higher and higher. Nowadays, all over the world are building a variety of garden projects and are constantly building. Many developers build projects because they have a business philosophy of following the crowd. However, most of these garden projects were of low quality, especially real estate. In order to repay the investment fund, many developers choose the high-speed development mode, and they will not consider the quality management of landscape engineering. Under the environment of high-speed requirements and a considerable workload, practitioners can only ensure that the quality of landscape projects meets the most basic requirements. However, with the development of society, human needs have become diversified, which not only needs to meet the basic needs of human practicality and economy but also needs to consider the needs of spirit and aesthetics. It also represents the standard of landscape quality because customers' needs are improving. At present, real estate landscape practitioners encounter many complaints about quality problems because they cannot meet customers' needs. In addition, the landscape quality also affects the decision-making of house buyers, that is, the house sales of developers. Therefore, developers and users pay more attention to the quality management of today's real estate landscape. However, there is often a contradiction between the work requirements of real estate landscape practitioners and customers' needs. Customers' needs are improving, but the practitioners' knowledge of project management, especially quality management, has iv not increased accordingly. This study found the challenges, influencing factors, and quality management tools of China's real estate landscape quality management through the literature review. Then, this study interviewed nine real estate landscape project experts to verify the conclusion of the literature review. For the customer demand, which is the most critical factor affecting China's real estate quality management, this study used the questionnaire method to investigate the residents' satisfaction with the landscape quality of phase I of project A and the potential buyers' demand for the landscape quality of phase II of project a. This study collects a large amount of data through mixed methods and verifies each other to ensure the effectiveness of the data. This study promotes Chinese real estate landscape practitioners to use improved quality management tools to implement customer demand-oriented quality management for landscape projects to improve landscape design and engineering quality. That is to provide practical improvement suggestions and methods for China's real estate landscape quality management. Indirectly contributing to solving the existing quality problems, improving the existing quality tools, increasing employees' quality management knowledge, and improving the industry quality standards.